1997
DOI: 10.2190/4x1b-6h51-m4jx-r7w8
|View full text |Cite
|
Sign up to set email alerts
|

Informational and Symbolic Content of over-the-Counter Drug Advertising on Television

Abstract: The informational and symbolic content of 150 over-the-counter drug commercials on television are empirically analyzed in this study. Results on the informational content suggest that over-the-counter drug ads tend to focus on the concern of what the drug will do for the consumer, rather than on the reasons why the drug should be ingested. Accordingly, advertising strategy is centered on consumer awareness of the product as the primary goal. Educational commitment, however, did not seem to be blended into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(23 reference statements)
0
19
0
1
Order By: Relevance
“…Tsao (1997) reviewed information and symbolic content in OTC advertisements aired on television and concluded that information in OTC ads was limited to the effects of the drug, not the reasons to take the drug, and that symbolic content in the ads reinforced the message that drugs were easy, quick fixes to common symptoms. No quantitative measurement of benefits or risks in the advertisements was included in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tsao (1997) reviewed information and symbolic content in OTC advertisements aired on television and concluded that information in OTC ads was limited to the effects of the drug, not the reasons to take the drug, and that symbolic content in the ads reinforced the message that drugs were easy, quick fixes to common symptoms. No quantitative measurement of benefits or risks in the advertisements was included in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new addition to media research is the content analysis of advertising for overthe-counter (OTC) and prescription drugs (Brownfield et al, 2004;Cline & Young, 2004;Kaphingst et al, 2004;Kirksey et al, 2004;Pinto, 2000;Tsao, 1997;also Miles, 1998, on commodified natural medicines). Given space limitations, I note only that concerns about these advertisements have not dissipated (Novelli, 1990) and reference other relevant advertising research throughout this review.…”
Section: Scope Of Popular Media Consideredmentioning
confidence: 99%
“…1,22 Four studies have investigated information or appeals in OTC drug advertising. [23][24][25][26] Although none of these studies used the same rubrics that were applied in the prescription drug ad studies, they revealed that for print advertising, OTC advertisements rarely (7% of ads) contained specific information on side effects or contraindications, but they contained high amounts of rational and persuasive content. 23,26 On television, most OTC advertisements (92%) contained only 2 informative cues, 24 and, like print advertisements, few ads (7%) contained specific side effects or contraindications.…”
Section: Introductionmentioning
confidence: 99%